The Difficulty To Distinguishing Between Embryonal Cell Carcinoma In The Anterior Mediastinal And Lung Adenocarcinoma - Fahmi, Kristia; Pratiwi, Suryanti Dwi; Setyawan, Ungky Agus (Malang Respiratory Journal, 2025)
Background: Frequently encountered malignant anterior mediastinal tumors include thymoma, lymphoma and germ-cell tumors. Non-seminomatous germ-cell tumors histologically classified as embryonal-cell carcinoma, choriocarcinoma, yolk sac tumor, teratoma1. Embryonal-cell carcinoma is an exceedingly rare case (8%) of primary mediastinal germ-cell tumors, with poor prognosis. Case Presentation: An 18-year-old-male presented with severe dyspnea, echocardiography revealed pericardial effusion, leading to emergency pericardiocentesis and pigtail catheter insertion, draining a total of 1900 cc serohemorrhagic fluid. Thoracic CT scan+contrast unveiled a big mass (10.6 x 17 x 14.4 cm) in the anterior-middle-left posterior mediastinal, causing compression left main bronchus, encasing the left pulmonary artery and aortic arch. Two challenging Trans-Thoracic Needle Aspiration (TTNA) attempts led to difficulty in distinguishing between Embryonal-cell Carcinoma and Adenocarcinoma. A multidisciplinary discussion leaned toward an Embryonal-cell Carcinoma diagnosis. Due to the patient's worsening state and impracticality of open biopsy, chemotherapy was initiated. The patient improved clinically, achieving stable disease based on RECIST criteria until the third chemotherapy cycle but experienced a decline in their condition after the fourth cycle. Discussion: Embryonal-cell carcinoma of the mediastinal is a rare condition4 with poor prognosis, with the three-year survival rate 47.4% and five-year survival rate 23%5. Achieving precise diagnosis by TTNA is challenging. Open biopsy and histopathological biomarkers play a pivotal role in identifying the cell type and determining appropriate therapy6. The patient initially exhibited favorable response to chemotherapy, which later decline after the fourth cycle. Conclusion: Precise diagnosis of embryonal-cell carcinoma provides certainty in treatment and improve survival rates. Keywords: Embryonal, Adenocarcinoma, Diagnosis